Efeito de doses de nitrogênio em gramíneas do gênero cynodon - Mendes, Leonardo Augusto (2000)
The experiment was conducted at the "Department of Animal Science, Universidade Federal de Lavras - UFLA" in the State of Minas Gerais - MG, and it was studied the effect of four nitrogen doses on dry matter production, gross protein content and production, and the content of FDN, FDA, N-FDN (%) and N-FDA (%), on the forage grasses Coastcross {Cynodon dactylon (L.) Pers x Cynodon nlemjuensis Vanderyst}, Tifton68 {Cynodon spp) and Tifton 85 {Cynodon spp). The nitrogen doses' used were:0, 100, 200 and 400 kg/ha of ammonium sulfate. The N fertilizer was broadcast over the soil. The soil used is classified as Dystrophic Dark Red with gentle slope, 12% Slope. At the beginning of the experiment, the soil was fertilized with P and K. The rj y experimental design utilized was a randomized complete block with six replications, and the treatments were distributed in a subdivided plot. The main qí plots were composed by the grasses and the subplots by the doses of nitrogen. The nitrogen fertilizerwas appliedseven days after each cutting date and thecut was performed at a height of lOcm above the soil, using a coastal mower.ÇThe cut interval was 42 days. Nitrogen fertilization enhanced both dry matter yield and crude protein content ofthe grasses studiedjj There was a decrease in the content ofNDF, N-NDF and N-ADF, but it dicWt alter the ADF ofthese grasses.